If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 3 = -3 + 2y + 14 Reorder the terms: 3 + 4y = -3 + 2y + 14 Reorder the terms: 3 + 4y = -3 + 14 + 2y Combine like terms: -3 + 14 = 11 3 + 4y = 11 + 2y Solving 3 + 4y = 11 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 3 + 4y + -2y = 11 + 2y + -2y Combine like terms: 4y + -2y = 2y 3 + 2y = 11 + 2y + -2y Combine like terms: 2y + -2y = 0 3 + 2y = 11 + 0 3 + 2y = 11 Add '-3' to each side of the equation. 3 + -3 + 2y = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 11 + -3 2y = 11 + -3 Combine like terms: 11 + -3 = 8 2y = 8 Divide each side by '2'. y = 4 Simplifying y = 4
| 2.25=qt | | 1-3x=2(-4x+7) | | 4a+2b=5 | | -10=-4+2k | | -5(x-4)-9=11 | | 14=8+2p | | 7(2x+5)=4x | | 10b^2-11b+3=0 | | 16=3s-4 | | 5+7i^2= | | (5x^2-7x-2)+(9x^2+8x-4)= | | 5(3y-1)-3(2x)=19 | | 6+3s=-9 | | 3m^2+6=-36 | | 3q+1=10 | | 2(n-6)=24 | | -6x+4=-4(2x+3) | | 2+3(x+1)=5x+5 | | 3(4x-3.2)=8x-9.6 | | 6+4f=46 | | 7.5(k-5)=22.5 | | y=2x^2+10 | | Y=-0.2X+33 | | a^2-10a+25=49 | | Y=-0.2X+30 | | Y=0.2X+33 | | 8-d(d+4)=3d-d(d+2)+5 | | 4k+5=29 | | 9+11=50x+4 | | 5=2w+3 | | 2s-3=1 | | 10x-4=50x+4 |